2022
DOI: 10.1111/febs.16587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural RNA modifications on the activity of SARS‐CoV‐2 RNA‐dependent RNA polymerase

Abstract: RNA‐dependent RNA polymerase (RdRp) plays a key role in the replication of RNA viruses, including SARS‐CoV‐2. Processive RNA synthesis by RdRp is crucial for successful genome replication and expression, especially in the case of very long coronaviral genomes. Here, we analysed the activity of SARS‐CoV‐2 RdRp (the nsp12–nsp7–nsp8 complex) on synthetic primer–templates of various structures, including substrates with mismatched primers or template RNA modifications. It has been shown that RdRp cannot efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
0
13
1
Order By: Relevance
“…In addition, experimental work on the nsp14 exonuclease enzyme of SARS-CoV-2 has shown that for excision of an incorrect nt, the nt needs to have a proper RNA sugar, 2’ and 3’ OH functional group [78], indicating that the enzyme may require some nucleotide selectivity to prevent dNTP’s from chemical incorporation. Furthermore, recent experimental studies have shown that an elongation complex soaked in solution with dNTPs had no catalytic activity [79]. Michaelis–Menten kinetics also showed the SARS-CoV-2 RdRp selectivity of ATP over dATP is ∼ 1000 ( = 0.02 in dATP and 23 in ATP) [80].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experimental work on the nsp14 exonuclease enzyme of SARS-CoV-2 has shown that for excision of an incorrect nt, the nt needs to have a proper RNA sugar, 2’ and 3’ OH functional group [78], indicating that the enzyme may require some nucleotide selectivity to prevent dNTP’s from chemical incorporation. Furthermore, recent experimental studies have shown that an elongation complex soaked in solution with dNTPs had no catalytic activity [79]. Michaelis–Menten kinetics also showed the SARS-CoV-2 RdRp selectivity of ATP over dATP is ∼ 1000 ( = 0.02 in dATP and 23 in ATP) [80].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent experimental studies have shown that an elongation complex soaked in solution with dNTPs had no catalytic activity. 89 Michaelis-Menten kinetics also showed the SARS-CoV-2 RdRp selectivity of ATP over dATP is B1000 ( V max K m ¼ 0:02 in dATP and 23 in ATP). 90 Similar trends were observed in PV in vitro biochemical studies with B117 discrimination factor…”
Section: Free Energetics Favor Insertion Of Cognate Ntps But Disfavor...mentioning
confidence: 92%
“…Most importantly, a nucleoside-modified base, 5-methylcytosine (5-MeC) was incorporated to reduce innate responses, resulting in reduced reactogenicity. 15 , 16 N1-Methylpseudouridine was utilized in existing mRNA vaccines to reduce the innate responses 17 , 18 ; however, N1-methylpseudouridine appears to inhibit the VEEV RNA-dependent RNA polymerase or transcriptase function. Therefore, innate responses were minimized in VLPCOV-02 by incorporation of 5-MeC, an approach supported by both preclinical in vitro and animal model observations.…”
Section: Introductionmentioning
confidence: 99%